Evaporation-induced self-assembly of quantum dots-based concentric rings on polymer-based nanocomposite films. Issue 40 (26th September 2016) - Zhang, Shaofu; Luan, Weiling; Zhong, Qixin; Yin, Shaofeng; Yang, Fuqian
Abstract : Fluorescence image of concentric rings, and variation of PL intensity with the position of concentric rings. Abstract : The "ball-on-film" template is used to construct concentric rings on the surface of PMMA-QDs (polymethyl methacrylate – quantum dots) nanocomposite films via the evaporation of pure chloroform droplets, which are confined by a steel ball. The concentric rings consist of QDs, as revealed by the fluorescence images of the concentric rings. The photoluminescence intensity of the concentric rings increases with the increase of the distance to the ball center, suggesting that the amount of QDs accumulated around the contact line at individual stick state increases with the increase of the distance to the ball center. Both the wavelength and cross-sectional area (width) of the concentric rings increase approximately linearly with increasing distance to the ball center, independent of the ball size, the film thickness and the QDs concentration. For the PMMA-QDs nanocomposite films prepared from the same QDs concentration in chloroform, the thicker the PMMA-QDs nanocomposite film, the larger the wavelength for the same distance to the ball center. The effect of confinement of two steel balls on the surface patterns over the PMMA-QDs nanocomposite films is studied via a template of "two spheres on film". Symmetric surface patterns are formed. There exist two types of featureless zone between the two balls, depending on the distance between the two balls: one is the inner featureless zone and the other is the outer featureless zone. The size of both featureless zones increases with the increase of the ball distance.